Demographic, Clinical, and Functional Factors Associated With Antidepressant Use in the Home Healthcare Elderly - Weissman, Judith (2011)
OBJECTIVES: Determine rates and demographic, clinical, and functional correlates of antidepressants (ADs) in home healthcare patients. METHODS: Year 2007 cross-sectional National Home Health and Hospice Care Survey (N = 3,226) of patients 65 years or older (mean 80.11, confidence interval [CI] = 79.65–80.57). RESULTS: Overall 33.50% used ADs. Among the 6.76% with depression, 70.84% used ADs compared with 29.15% who used ADs without a documented depression diagnosis. In a regression, controlling for depression, blacks used less ADs than whites (odds ratio [OR] = 0.41, CI = 0.24–0.70). Younger age (OR = 0.96, CI = 0.94–0.98), activities of daily living impairments (OR = 1.15, CI = 1.05–1.26), benzodiazepines (OR = 2.63, CI = 1.88–3.69), antipsychotics (OR = 2.08, CI = 1.29–3.36), and nonpsychotropics (OR = 1.07, CI = 1.04–1.10) were related to AD use. CONCLUSION: Among home healthcare patients, more than one-third took ADs including patients without depression. Blacks used fewer ADs than whites. Increased use was associated with younger age, disability, and nonpsychotropics.